2020
DOI: 10.31234/osf.io/eyjv7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Investigating the effect of heartrate synchrony on prosocial behaviour towards a robot

Abstract: Robots are being designed to alleviate the burden of social isolation and loneliness, particularly for older adults for whom these issues are more widespread. While good intentions underpin these developments, the reality is that many of these robots are abandoned within a short period of time. To encourage the longer-term use and utility of such robots, researchers are exploring ways to increase robot likability and facilitate attachment. Results from experimental psychology suggest that interpersonal synchro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…To further investigate whether these undeniably prosocial feelings persist, or change over time, or whether it is possible for those reporting no emotional attachment toward the robot to develop attachment, longitudinal data collection would be required (c.f. Riddoch and Cross, 2020). To better understand individual differences in attachment to robots, it would also be insightful to collect more information from participants regarding their personality and background.…”
Section: Feelings Of Connectionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further investigate whether these undeniably prosocial feelings persist, or change over time, or whether it is possible for those reporting no emotional attachment toward the robot to develop attachment, longitudinal data collection would be required (c.f. Riddoch and Cross, 2020). To better understand individual differences in attachment to robots, it would also be insightful to collect more information from participants regarding their personality and background.…”
Section: Feelings Of Connectionmentioning
confidence: 99%
“…It could be suggested that if a robot were deployed in a certain setting, and programmed to behave in a consistent way, that there could be wide scale acceptance and usage, but without an appreciation for individual differences and changes in attitudes over time, we argue that this is unlikely to be the case. Despite being a complicated venture, a better understanding how humans perceive robots, and how these feelings evolve across time (e.g., Riddoch and Cross, 2020) is becoming increasingly important, as in some instances, it could be inappropriate/ harmful to for humans to feel attached to robots -e.g., military personnel with bomb-disposal robots, or vulnerable people with care robots (Sharkey and Sharkey, 2012;Darling, 2015;Lin et al, 2017).…”
Section: Pepper the Robot As More Than An Objectmentioning
confidence: 99%